A Replica Detection Scheme Based on the Deviation in Distance Traveled Sliding Window for Wireless Sensor Networks. (15th January 2017) - Mishra, Alekha Kumar; Tripathy, Asis Kumar; Kumar, Arun; Turuk, Ashok Kumar
Abstract : Node replication attack possesses a high level of threat in wireless sensor networks (WSNs) and it is severe when the sensors are mobile. A limited number of replica detection schemes in mobile WSNs (MWSNs) have been reported till date, where most of them are centralized in nature. The centralized detection schemes use time-location claims and the base station (BS) is solely responsible for detecting replica. Therefore, these schemes are prone to single point of failure. There is also additional communication overhead associated with sending time-location claims to the BS. A distributed detection mechanism is always a preferred solution to the above kind of problems due to significantly lower communication overhead than their counterparts. In this paper, we propose a distributed replica detection scheme for MWSNs. In this scheme, the deviation in the distance traveled by a node and its replica is recorded by the observer nodes. Every node is an observer node for some nodes in the network. Observers are responsible for maintaining a sliding window of recent time-distance broadcast of the nodes. A replica is detected by an observer based on the degree of violation computed from the deviations recorded using the time-distance sliding window. The analysis and simulation results show that the proposed scheme is able to achieve higher detection probability compared to distributed replica detection schemes such as Efficient Distributed Detection (EDD) and Multi-Time-Location Storage and Diffusion (MTLSD).